THE IMPACT OF ENTREPRENEURIAL ORIENTATION ON KNOWLEDGE MANAGEMENT - Purnama, Ady; Harlianto, Jefta; Herlina, Maria Grace (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract - The growing competitive global business environment has increasingly identified Knowledge Management (KM) as a crucial strategic approach. The connection between Entrepreneurial Orientation (EO) and KM has not been thoroughly investigated, and there are only a few empirical studies on this subject. The primary goal of this study is to examine, through empirical means, the substantial influence of entrepreneurial orientation (EO) on knowledge management (KM). Using a quantitative approach, information was gathered via surveys from 133 staff members at a college or university and then assessed using Smart PLS. The findings reveal that innovation, risk-taking, and proactiveness are key elements of entrepreneurial orientation (EO) and significantly impact knowledge management (KM). The findings emphasize the critical importance of EO in improving KM operations within companies. This study provides new insights into the relationship between entrepreneurship and knowledge management by presenting empirical evidence, showing the vital role of entrepreneurial orientation in driving knowledge management. The study adds to the current body of knowledge and offers significant insights for professionals, academics, and business owners regarding the significance of combining entrepreneurial orientation and knowledge management to gain competitive benefits. Keywords: Entrepreneurial Orientation; Knowledge Management; Innovation; Risk-taking; Proactiveness